Good health and well-being for the sustainable development of Moscow: state and prospects - V. M. Kuraeva (Здоровье мегаполиса)
Introduction. "Health and well-being of people" is the first national development goal of the Russian Federation until 2030. The Sustainable Development Goals (SDGs), also known as the Global Goals adopted by the United Nations (UN) in 2015, are comprehensive and indivisible and are being implemented everywhere [1]. At the 2016 Shanghai Conference on Healthy Cities, people's health and well-being were placed at the center of the UN's 2030 Agenda for Sustainable Development (“Agenda 2030”). A preliminary assessment of the current state and current trends using the example of Moscow can be a “starting point” for making decisions in the field of public health management in large cities.Goal. To assess the progress of the city of Moscow towards achieving the third sustainable development goal (SDG 3).Materials and methods. For the analysis, data from open sources of the Federal State Statistics Service of Russia, the Rospotrebnadzor department for the city of Moscow were used.Results. Despite the pandemic, Moscow has maintained positive trends on a number of SDG targets and is advancing ahead (the proportion of births attended by skilled health workers; reducing infant and child mortality and tuberculosis incidence). There is also a decrease in mortality from traffic accidents, diseases of the circulatory system and neoplasms, primary incidence of malaria and hepatitis B. The assessment of public health indicators at the Moscow level is a new step in regional and territorial management through the use of the SDG 3 operational tool.